Pengaruh Harga, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy Di Astra Motor Sepinggan - Ayu Rahmawati , Putri; Hasan, Syajril; Taufik Rohman, Dwi (Fakultas Ekonomi Universitas Balikpapan, 2026)
This study aims to analyze the effect of price, brand image, and product quality on purchasing decisions for Scoopy motorcycles at Astra Motor Sepinggan. A quantitative approach was employed using purposive sampling, involving 79 respondents determined by the Isaac and Michael formula. Data were collected through a Likert scale and analyzed using multiple linear regression. The results indicate that price, brand image, and product quality each have a positive effect on purchasing decisions.